2021
DOI: 10.3389/fneur.2020.608838
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Filling Defect in Posterior Semicircular Canal on MRI With Balanced Steady-State Gradient-Echo Sequences After Labyrinthine Ischemia in the Common Cochlear Artery Territory as an Early Sign of Fibrosis

Abstract: We describe a rare case of posterior semicircular canal (PSC) fibrosis following acute labyrinthine ischemia in the territory supplied by the common cochlear artery (CCA) and review the relevant literature. A 71-year-old man with multiple vascular risk factors presented 12 days after the onset of acute vertigo and profound left-sided hearing loss. Right-beating spontaneous nystagmus with downbeat components elicited by mastoid vibrations and headshaking was detected. The video head impulse test (vHIT) revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Therefore, the clinical and instrumental effects of PVA occlusion perfectly overlap with IVN. While in the case described by Castellucci et al (38), an occlusion of CCA was suggested to explain the involvement of the lower labyrinthine structures and PSC fibrosis, a possible PVA terminal occlusion seems to represent the possible site of vascular lesion in our case, resulting in acute PSC and saccular impairment without auditory symptoms. Since our patient denied previous infections, trauma, surgery, and middle/inner ear dysfunctions other than previous contralateral sudden sensorineural HL, most conditions accounting for LO could be reasonably excluded, while inner ear ischemia seems to represent the most likely pathomechanism.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Therefore, the clinical and instrumental effects of PVA occlusion perfectly overlap with IVN. While in the case described by Castellucci et al (38), an occlusion of CCA was suggested to explain the involvement of the lower labyrinthine structures and PSC fibrosis, a possible PVA terminal occlusion seems to represent the possible site of vascular lesion in our case, resulting in acute PSC and saccular impairment without auditory symptoms. Since our patient denied previous infections, trauma, surgery, and middle/inner ear dysfunctions other than previous contralateral sudden sensorineural HL, most conditions accounting for LO could be reasonably excluded, while inner ear ischemia seems to represent the most likely pathomechanism.…”
Section: Discussionmentioning
confidence: 50%
“…Selective ossification of a single semicircular canal is very rare. Castellucci et al (38) were recently able to demonstrate a filling defect in the PSC on MRI, consistent with early fibrosis of the canal, in a patient with a sudden cochleovestibular loss likely due to CCA ischemia. A labyrinthine ossification was clearly demonstrated two months after vascular inner ear occlusion in guinea pigs by Kimura and Perlman (39,40).…”
Section: Discussionmentioning
confidence: 79%
“…It has been suggested that posterior SCC paresis associated with ipsilateral sudden hearing loss could possibly be caused by ischemia of the common cochlear artery ( 37 ), while the lesion pattern of hearing loss and ipsilateral paresis of the posterior and horizontal SCCs may indicate viral neurolabyrinthitis ( 16 ). Recently, a selective vHIT gain reduction of the ipsilateral posterior SCC in a SSNHL patient with acute vertigo has been reported, in which posterior SCC fibrosis has been detected by inner ear MRI, thus lend further support to vascular etiology ( 38 ). Although recent application of instrumental testing (vHIT and VEMP) can facilitate topographical diagnosis of selective dysfunction of inner ear end-organs, the underlying mechanisms require further investigations for patients with vertigo in SSNHL ( 3 , 38 ).…”
Section: Discussionmentioning
confidence: 88%
“…Recently, a selective vHIT gain reduction of the ipsilateral posterior SCC in a SSNHL patient with acute vertigo has been reported, in which posterior SCC fibrosis has been detected by inner ear MRI, thus lend further support to vascular etiology ( 38 ). Although recent application of instrumental testing (vHIT and VEMP) can facilitate topographical diagnosis of selective dysfunction of inner ear end-organs, the underlying mechanisms require further investigations for patients with vertigo in SSNHL ( 3 , 38 ).…”
Section: Discussionmentioning
confidence: 88%
“…Isolated posterior canal dysfunction has also been reported in other conditions such as idiopathic sudden sensorineural hearing loss, 21 posterior semicircular canal aplasia, 22 and labyrinthine ischemia in the common cochlear artery territory. 23 The participants in our study were neither elderly individuals nor did they have any history of vestibular complaints or any of the vestibular pathologies just mentioned. Thus, it is unlikely that the reduced VOR gain in the posterior SCC (in our study) could have been due to isolated posterior canal lesions, as seen in some elderly individuals with vestibular complaints.…”
Section: Discussionmentioning
confidence: 95%